PINK1/Parkin-Dependent Mitochondrial Surveillance: From Pleiotropy to Parkinson's Disease - Mouton-Liger, Francois; Jacoupy, Maxime; Corvol, Jean-Christophe; Corti, Olga (Frontiers in Molecular Neuroscience, 2017)
Parkinson’s disease (PD) is one of the most frequent neurodegenerative disease caused by the preferential, progressive degeneration of the dopaminergic (DA) neurons of the substantia nigra (SN) pars compacta. PD is characterized by a multifaceted pathological process involving protein misfolding, mitochondrial dysfunction, neuroinflammation and metabolism deregulation. The molecular mechanisms governing the complex interplay between the different facets of this process are still unknown. PARK2/Parkin and PARK6/PINK1, two genes responsible for familial forms of PD, act as a ubiquitous core signaling pathway, coupling mitochondrial stress to mitochondrial surveillance, by regulating mitochondrial dynamics, the removal of damaged mitochondrial components by mitochondria-derived vesicles, mitophagy, and mitochondrial biogenesis. Over the last decade, PINK1/Parkin-dependent mitochondrial quality control emerged as a pleiotropic regulatory pathway. Loss of its function impinges on a number of physiological processes suspected to contribute to PD pathogenesis. Its role in the regulation of innate immunity and inflammatory processes stands out, providing compelling support to the contribution of non-cell-autonomous immune mechanisms in PD. In this review, we illustrate the central role of this multifunctional pathway at the crossroads between mitochondrial stress, neuroinflammation and metabolism. We discuss how its dysfunction may contribute to PD pathogenesis and pinpoint major unresolved questions in the field.